Price dynamics in artificial stock market with realistic order book mechanism - Cetin, Uzay; Demirtas, Sukru C.; Sahin, Senem Cakmak (ELSEVIER SCIENCE INC, 2025)
We analyzed the effect of the daily price margin on artificial stock markets. In our study, we have two distinct market scenarios: One designed to imitate a market akin to that of T & uuml;rkiye, characterized by the presence of a daily price margin regulation, and the other reflecting a market resembling the United States, where orders are not subject to daily price margin constraints. With daily price margin regulations stock prices become more accessible, positively impacting market volume. We incorporated a realistic order book mechanism for keeping track of the bid and ask orders. Traders are classified as either fundamental or noise, according to their strategies. We have also established a dynamic risk level for each stock, based on its weekly transaction volumes. Only fundamentals are risk-aware. That is, they tend to order stocks with low risk and avoid high risk stocks. We have detected emerging patterns of price fluctuations within the market scenario governed by the daily price margin regulations. Risk-aware herd behavior, despite not being explicitly modeled as an input, emerges also spontaneously within the system. These patterns emerge because of the complex relationship among dynamic risk levels of stocks, risk-aware traders and the daily price margin regulation.
Keywords: Artificial stock market; Agent-based financial modeling; Multi-agent system; Realistic orderbook; Price margin; Business & Economics